A fiber bragg grating-based gap elongation sensor for the detection of gap elongation in bolted flange connection - Nur Ainaa Adhreena, Muhamad Shukri; Mohd Hafizi, Zohari; Vorathin, E. (Penerbit UTHM, 2022)
Many attempts have been made by embedding a strain gauge sensor into the bolt shank to directly monitor the looseness of bolted structures. This application is constrained by many factors, including massive cabling connection, shortcomings of this sensor in harsh conditions, and low efficiency for high temperature applications. Therefore, fiber Bragg grating (FBG) sensing technology is a good alternative to solve the problem. In this article, an FBG-based gap elongation sensor was developed by embedding the sensor into a Teflon tube and clamping on the metal base structure. Several tests were carried out to calibrate the strain-sensitive coefficient of the sensor and also to determine the stability, linearity, and repeatability of the sensor for gap strain measurement. The strain sensitivity of the sensor was determined by a standard tensile test, with the strain sensitivity values ranging from 0.4221 pm/με to 0.5245 pm/με. During the calibration test, the FBG sensors showed excellent linearity and repeatability of less than 0.1% and 5% errors, respectively. The experimental results demonstrated a linear relationship between the applied force and the FBG sensor wavelength. Furthermore, the experimental results demonstrated acceptable linearity and stability of the sensor when subjected to bending loads with overall repeatability errors of less than 10%. This proposed method provides an alternative approach to monitor bolted gap elongation and characterize bolt looseness.